Practical mobile forensics : a hands-on guide to mastering mobile forensics for the iOS, Android, and Windows Phone platforms /: a hands-on guide to mastering mobile forensics for the iOS, Android, and Windows Phone platforms. (2016) - Mahalik, Heather; Bommisetty, Satish; Tamma, Rohit
No abstract available